L’agriculture oasienne à l’époque perse dans le sud de l’oasis de Kharga (Égypte, ve-ive s. AEC) - Claire Newton; Thomas Whitbread; Damien Agut-Labordère; Michel Wuttmann† (Revue d'ethnoécologie, 2013)
The archaeobotanical study of several rural settlement sites in the southern Kharga Oasis allows us to present an overview of agriculture during the century following the first establishment of an irrigated area in the 5th c. BCE. The oasis agricultural system is a type of agroforestry, integrating a particular combination of palms and other fruit crops with annual crops and livestock. Especially distinctive are the association of three species of palms, including the native doum and argun palms, and the role of cash crops.